Navigating Technological Turbulence: A Systematic Review on SMEs’ Digital Capabilities and Market Performance - Putri, Arimbi Kaniasih; Indrayana, Adimas Bagus; Isnaini, Santi; Mawariza, Putri Suci (International Journal of Multidisciplinary Research of Higher Education, 2026)
The acceleration of digital transformation has created technological turbulence that challenges the sustainability of Small and Medium Enterprises. This systematic review aims to analyze how digital literacy, digital situational perception, self-efficacy, and organizational innovation collectively influence market performance under conditions of technological turbulence. Employing the PRISMA 2020 methodology, the study synthesizes evidence from 15 high-quality empirical studies. Findings reveal that digital literacy and digital situational perception serve as foundational individual capabilities enabling effective technological adaptation, while self-efficacy strengthens confidence in decision-making and fosters innovative risk-taking. Organizational innovation functions as a mediating mechanism that transforms individual capabilities into competitive advantage through dynamic capabilities. Technological turbulence emerges as a complex moderating factor—enhancing positive relationships in agile organizations but constraining those less adaptive. Theoretical contributions include the development of an integrative framework bridging self-efficacy theory and dynamic capabilities. Practically, the study offers strategic guidance for strengthening SME capacity and designing holistic policy support. Future research agendas highlight the need to explore causal mechanisms and longitudinal dynamics within the continuously evolving context of digital transformation.